2016
DOI: 10.1038/srep35693
|View full text |Cite
|
Sign up to set email alerts
|

Performance and microbial ecology of a nitritation sequencing batch reactor treating high-strength ammonia wastewater

Abstract: The partial nitrification (PN) performance and the microbial community variations were evaluated in a sequencing batch reactor (SBR) for 172 days, with the stepwise elevation of ammonium concentration. Free ammonia (FA) and low dissolved oxygen inhibition of nitrite-oxidized bacteria (NOB) were used to achieve nitritation in the SBR. During the 172 days operation, the nitrogen loading rate of the SBR was finally raised to 3.6 kg N/m3/d corresponding the influent ammonium of 1500 mg/L, with the ammonium removal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 42 publications
(46 reference statements)
0
11
0
Order By: Relevance
“…Moreover, Firmicutes was reported to be predominant in autotrophic denitrification biocathode and hydrogenotrophic denitrification under thermophilic (30 o C) conditions (Wang et al, 2015;Xiao et al, 2015). Bacteroidetes was found to be dominant in prior nitritation and partial nitritation processes (Chen et al, 2016). From the present study, it is demonstrated that the microorganisms in both reactors were detected in the denitrification and the microorganisms could use hydrogen gas as the electron donor for nitrate removal.…”
Section: Microbial Communitymentioning
confidence: 49%
“…Moreover, Firmicutes was reported to be predominant in autotrophic denitrification biocathode and hydrogenotrophic denitrification under thermophilic (30 o C) conditions (Wang et al, 2015;Xiao et al, 2015). Bacteroidetes was found to be dominant in prior nitritation and partial nitritation processes (Chen et al, 2016). From the present study, it is demonstrated that the microorganisms in both reactors were detected in the denitrification and the microorganisms could use hydrogen gas as the electron donor for nitrate removal.…”
Section: Microbial Communitymentioning
confidence: 49%
“…wastewater treatment. It is an attractive technology to treat this type of pollution due to economic advantages it offers in terms of operation cost and efficiency [8,9]. However, the treatment sites require a great deal of land and are costly to maintain, and the treatment process itself requires a lot of attention.…”
Section: Introductionmentioning
confidence: 99%
“…However, the treatment sites require a great deal of land and are costly to maintain, and the treatment process itself requires a lot of attention. [8][9][10]. Thus, alternatives have been introduced such as the sequencing batch reactor (SBR).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…7,8 In recent years, various methods, such as breakpoint chlorination method, [9][10][11] ion exchange adsorption, 12 biological method, 13,14 and chemical precipitation, 15 have been developed for treatment of ammonia wastewater. These methods have advantages, but there are still some flaws, [16][17][18][19][20][21] such as high cost, producing secondary pollution, low removal efficiency, long processing time, high energy consumption, and limited treatment capacity. Therefore, it is of vital significance to develop a new treatment technology for ammonia wastewater.…”
Section: Introductionmentioning
confidence: 99%